2017
DOI: 10.4269/ajtmh.16-0935
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya Detection during Dengue Outbreak in Sumatra, Indonesia: Clinical Manifestations and Virological Profile

Abstract: Chikungunya fever (CHIK) is an acute viral infection caused by infection with chikungunya virus (CHIKV). The disease affects people in areas where certain species mosquito vectors are present, especially in tropical and subtropical countries. Indonesia has witnessed CHIK disease since the early 1970s with sporadic outbreaks occurring throughout the year. The CHIK clinical manifestation, characterized by fever, headache, and joint pain, is similar to that of dengue (DEN) disease. During a molecular study of a D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 29 publications
2
34
0
Order By: Relevance
“…As has been noted in multiple studies [8,22,23,[30][31][32], it can be difficult, particularly in endemic regions, to identify an infecting arbovirus based solely on clinical presentation. The current study made use of a school cohort, and consequently ages were concentrated between 3 years and 20 years, reflecting attendance in prekindergarten through "grade 13" (an additional year of school generally taken as part of the secondary education cycle).…”
Section: Discussionmentioning
confidence: 99%
“…As has been noted in multiple studies [8,22,23,[30][31][32], it can be difficult, particularly in endemic regions, to identify an infecting arbovirus based solely on clinical presentation. The current study made use of a school cohort, and consequently ages were concentrated between 3 years and 20 years, reflecting attendance in prekindergarten through "grade 13" (an additional year of school generally taken as part of the secondary education cycle).…”
Section: Discussionmentioning
confidence: 99%
“…The application of Bayesian statistical inference framework, can allow the reconstruction of the geographic history of the still ongoing and never reported before epidemic on the basis of the first isolates sampled at known times . It has been showed that CHIKV was imported to the Americas from South‐East Asia …”
Section: Phylogenesis and Phylodynamic Of Arbovirusesmentioning
confidence: 99%
“…180 It has been showed that CHIKV was imported to the Americas from South-East Asia. [181][182][183][184][185] During CHIKV outbreak in 2005 and 2006, nonsynonymous mutation (A226V) occurred both on La Reunion and in some Indian CICCOZZI ET AL.…”
Section: The Phylogeny Of Genotypes B and Cmentioning
confidence: 99%
“…Of note, compared to the amino acid sequence of Ross, a 7-aa deletion was observed in the nsP3 of SZ1239, which was also found in other studies (GenBank accession no. HE806461, KM673291, and KX097982) ( 7 9 ). In addition, in the 3′ UTR of SZ1239, only two RSEs were observed, similar to those of the three CHIKV isolates mentioned above ( 7 9 ).…”
Section: Genome Announcementmentioning
confidence: 99%
“…HE806461, KM673291, and KX097982) ( 7 9 ). In addition, in the 3′ UTR of SZ1239, only two RSEs were observed, similar to those of the three CHIKV isolates mentioned above ( 7 9 ). No A226V mutation in the envelope protein E1 was found in either strain.…”
Section: Genome Announcementmentioning
confidence: 99%